Shared decision making - a review of its evaluation, efficacy, and applicability in asthma - Piątkowska, Adrianna; Marszałek, Kamil; Krupińska, Natalia; Malaya, Elizabeth; Adamczewska, Magdalena; Kuna, Piotr; Panek, Michał (Frontiers in Medicine, 2025)
Over the years, the approach to medical decision-making has evolved significantly–from the traditional paternalistic model, in which decisions were made on behalf of the patient, to Shared Decision Making (SDM), which actively involves patients in the process. Given that a strong patient–healthcare provider relationship is a key factor in effective treatment, the literature increasingly highlights the importance of incorporating patient preferences. To achieve this, patients must receive clear explanations about their condition and treatment options, as well as care plans tailored to their individual needs. This is particularly relevant in conditions requiring long-term treatment, where outcomes depend heavily on patient adherence, motivation, and consistency. Chronic diseases like asthma require ongoing cooperation and trust between patients and healthcare providers. Asthma, one of the most common chronic respiratory conditions, has no curative treatment; its management relies on daily inhaled medications to control symptoms and prevent exacerbations. Several models have been developed to structure SDM implementation, ranging from basic frameworks promoting engagement to comprehensive approaches emphasizing environmental readiness and professional education. Key components include blended learning for healthcare providers and standardized tools to operationalize SDM, such as Patient Decision Aids (e.g., Written Asthma Action Plans) and multilingual resources like “Asthma Australia.” These tools are particularly valuable in overcoming barriers such as language and cultural differences, which can hinder access to care–especially for minority groups. Discrimination and lack of tailored communication can disproportionately affect patients with intellectual disabilities and those from culturally diverse backgrounds, highlighting the need for inclusive, individualized approaches in SDM-based chronic disease care. Although SDM shows promise in improving patient satisfaction, adherence, and potentially reducing healthcare costs, robust evidence remains limited. Global studies are needed to assess its true efficacy across various chronic conditions. This review aims to systematically analyze SDM models described in the literature, align them with asthma management requirements, incorporate patient needs and expectations, and propose practical strategies for integrating SDM in asthma care and other chronic respiratory diseases. Trust in healthcare providers is associated with improved health outcomes and increased treatment adherence, like for example “Asthma Australia” barriers to satisfactory care remain, particularly for patients from minority groups, who often face linguistic challenges, The structured integration of Shared Decision-Making (SDM). Although SDM has the potential to enhance patient satisfaction, improve adherence, and reduce healthcare costs is promising, conclusive evidence remains limited. The potential gain is not however excluded. There is a need for more data from studies on global scale to objectively determine its efficacy and applicability in various chronic conditions.